Radiofrequency characteristics of ionized sputtered tantalum nitride thin-film resistor in CMOS device - Sul, Woo Suk; Kwon, Soon Hyeong; Choi, Eunmi; Cui, Yinhua; Lee, Kang Won; Shim, Ho Jae; Gao, Yuan; Hahn, Sang June; Pyo, Sung Gyu (Electronic materials letters, 2017)
We report the analysis of the radiofrequency (RF) characteristics according to the size, area, and shape of TaN thin-film resistor (TFR) layers. As the TFR size increased, its characteristics were degraded with increasing frequency owing to the increased capacitive parasitic components. As the frequency increased from 1 MHz to 10 GHz, the effective resistance decreased by approximately 12.5%, 16.4%, and 37.8% when the resistor widths and lengths were 0.5 × 20, 1 × 40, and 2 × 80 μm, respectively. To optimize the performance of the high-frequency TFR, ensuring RF isolation via sufficient separation from the silicon substrates was crucial. To realize this RF isolation, methods for minimizing the effect of lossy Si substrates by using TFRs with a smaller area or by forming a patterned ground shield should be introduced.